EVALUATING THE LONG-TERM STORAGE TIME VIABILITY AND SIZE DYNAMICS OF BACILLUS SP. BIOENCAPSULATION IN SODIUM ALGINATE MATRIX - Saputra, Mochammad Mirza; Wuryandari, Yenny; Rahmadhini, Noni; Lestari, Safira Rizka (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2023)
The use of biological agents such as Bacillus sp. bacteria has begun to be widely used by farmers as a new form of control. Bacillus sp. needs to require special methods in its application because it has certain living conditions, and Bacillus sp. is vulnerable to environmental pressures. Bioencapsulated formulation in the form of granules is considered effective as a form of bacterial application in soil because it is able to protect Bacillus sp. and maintain survival. This study aims to determine the best concentration of sodium alginate in maintaining the viability of Bacillus sp. at the in vitro stage and to see changes in the size of the beads. The beads were made using extrusion method by combining Bacillus sp. suspension and sodium alginate suspension at 1%, 1.5%, and 2% concentration. The concentration of sodium alginate was not a major factor in changes in bead size and viability test results experienced significant changes in each observation. 1.5% and 2% concentrations can reach the highest viability value of 3x106 CFU/mL and decreased during 1 month of observation. Changes in bead size and viability were caused by the alginase enzyme produced by Bacillus sp.